Peningkatan Kemampuan Berbahasa Inggris Bagi Anak-Anak Didesa Pekik Nyaring - Dwi putra, Muhammad Chafri eza; Rullyanti, Merry; Putra, Dhanu Ario; Sumantri, Ajis (Jurnal Gotong Royong, 2024)
. Pekik Nyering Village is an area located in Pondok Kelapa District, Central Bengkulu Regency, where it is said that people who first entered this area heard screams that were very loud and could be heard everywhere, but the person who shouted was unknown and invisible. So that the mysterious incident experienced by our predecessors was used as the name of a region, namely the Pekik Nyering Region. According to information from several village elders, the origins of Pekik Nyering Village began in 1956 with the arrival of transmigration from Java as many as 230 families and their placement spread throughout Pekik Village. Nyaring, so that Pekik Nyering Village has 4 blocks because the population is spread across four areas and each area is led by a stakeholder. In this new area, Transmigration residents build their territory to organize their lives. It turns out that in their life journey they experience many obstacles both from within and from outside, such as disturbances in the form of animals, nature and the environment. The children in this village still have low English language skills, so based on the results of observations, they need to be trained. And the results of the Real Work Lecture activities in this village were able to improve children's English language skills even though they were not optimal due to time constraints.